1986
DOI: 10.1172/jci112442
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell injury due to copper-catalyzed hydrogen peroxide generation from homocysteine.

Abstract: We have examined whether the toxic effects of homocysteine on cultured endothelial cells could result from the formation and action of hydrogen peroxide. In initial experiments with a cellfree system, micromolar amounts ofcopper were found to catalyze an oxygen-dependent oxidation of homocysteine. The molar ratio of homocysteine oxidized to oxygen consumed was 4.0, which suggests that oxygen was reduced to water. The addition of catalase, however, decreased oxygen consumption by nearly onehalf, which suggests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
449
2
19

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 791 publications
(486 citation statements)
references
References 33 publications
16
449
2
19
Order By: Relevance
“…41 It is likely, therefore, that HHcy decreases nitric oxide bioavailability through alternative mechanisms, such as accelerated oxidative inactivation of nitric oxide. 40 Homocysteine-induced oxidative inactivation of nitric oxide has been observed in vitro in cultured endothelial cells, 42 and evidence for increased oxidative inactivation of nitric oxide during HHcy has been obtained in animals using both pharmacological 41,[43][44][45][46] and genetic 47,48 approaches. Several types of reactive oxygen species (ROS), including superoxide, hydrogen peroxide, and peroxynitrite, may contribute to the oxidative inactivation of endothelium-derived nitric oxide in HHcy.…”
Section: Hhcy and Endothelial Cell Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 It is likely, therefore, that HHcy decreases nitric oxide bioavailability through alternative mechanisms, such as accelerated oxidative inactivation of nitric oxide. 40 Homocysteine-induced oxidative inactivation of nitric oxide has been observed in vitro in cultured endothelial cells, 42 and evidence for increased oxidative inactivation of nitric oxide during HHcy has been obtained in animals using both pharmacological 41,[43][44][45][46] and genetic 47,48 approaches. Several types of reactive oxygen species (ROS), including superoxide, hydrogen peroxide, and peroxynitrite, may contribute to the oxidative inactivation of endothelium-derived nitric oxide in HHcy.…”
Section: Hhcy and Endothelial Cell Dysfunctionmentioning
confidence: 99%
“…The highly reactive thiol group of homocysteine is readily oxidized to form ROS, 42 suggesting that homocysteine induces cell injury/dysfunction through a mechanism involving auto-oxidation and oxidative damage. However, this hypothesis fails to explain why cysteine, which is present in plasma at much higher concentrations than homocysteine and is readily auto-oxidized, does not cause endothelial cell injury and is not considered a risk factor for cardiovascular disease.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…The pro-oxidant hypothesis for homocysteine is based largely on results from in vitro studies. When exposed to free homocysteine at high (supraphysiological) concentrations, endothelial cells in culture show a loss of structural and functional integrity that can be mitigated by the presence of additional antioxidants (Starkebaum & Harlan, 1986;Blundell et al, 1996). The deleterious effects of homocysteine on endothelial cells in culture may be mediated by the increased production of superoxide radicals resulting from the autooxidation of homocysteine (Lang et al, 2000).…”
Section: Effect On Antioxidant Activitymentioning
confidence: 99%
“…One such mechanism invokes the potentially pro-oxidative potential of homocysteine, and argues that the increasing plasma concentrations of this amino acid are associated with increased oxidative stress and ensuing tissue damage (Bellamy & McDowell, 1997). Results from in vitro studies are generally supportive of a pro-oxidative role of homocysteine (Hirano et al, 1994;Starkebaum & Harlan, 1986), but the relevance of these observations to conditions in vivo are not known. Relatively few studies have explored this role for homocysteine in vivo and these have concentrated almost exclusively on events associated with greatly elevated plasma tHcy concentrations in patients with genetically determined homocystinuria, or with a transient acute elevation of plasma tHcy following an oral load of methionine Wilcken et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro high levels of homocysteine can generate HiO-> and the vasotoxic properties of homocysteine through lipid peroxidation have been proposed [15]. However, in plasma from patients with severe hyper homocysteinaemia no increase in lipid peroxidation could be found [16,17], Several in vitro studies with endothelial cells have shown cell dysfunction when homocysteine is added to the medium.…”
Section: Introductionmentioning
confidence: 99%